ANALISIS FITOKIMIA EKSTRAK DAUN BAJAKAH (Poikilospermum suaveolens (Blume) Merr) DARI DESA KAPIROE KECAMATAN PALOLO KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Bandy, Nur Afni; Erniwati, Erniwati; Muthmainnah, Muthmainnah; Ariyanti, Ariyanti; Hapid, Abdul; Asniati, Asniati (Universitas Tadulako, 2021)
The Bajakah plant (Poikilospermum suaveolens (Blume) Merr) is a plant that grows a lot in the tropics, in Indonesia itself is known for its tropical climate. traditions and community beliefs. Bajakah plants can be found in Sulawesi, to be precise, in Kapiroe Village, Palolo District, Sigi Regency, Central Sulawesi Province. This research was conducted from November to December 2020 for 96% ethanol solvent and continued in March 2021 for n-hexane solvent at the Research Laboratory of the Department of Chemistry, Faculty of Mathematics and Natural Sciences, Tadulako University. The method used in this study was the manufacture of Bajakah leaf powder (Poikilospermum suaveolens (Blume) Merr), analysis of the moisture content of the Bajakah leaf samples, extraction of the Bajakah leaf samples by maceration and identification of the chemical content of the maceration results of the Bajakah leaves using phytochemical tests such as the flavonoid test, test alkaloid, saponin test, tannin test, carotenoid test, terpenoid test and steroid test. The results of the water content of the leaves of bajakah (Poikilospermum suaveolens (Blume) Merr) were 11.26%. The phytochemical test analysis contained in the leaf extract of bajakah (Poikilospermum suaveolens (Blume) Merr) using 96% ethanol solvent is positive for alkaloid compounds, saponins, tannins, terpenoids while for positive n-hexane solvent contains tannins, steroids and carotenoids.Keywords:phytochemical analysis, extract, Poikilospermum suaveolens (Blume) Merr